Outcome of laser Treatment for Retinopathy of Prematurity: Oral Presentation - Observational Study - Ophthalmologist - IDAYANI PANGGALO (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Retinopathy of prematurity is a proliferative disorder that requires urgent treatment. Proper case finding and treatment will prevent permanent blindness in infants. Laser photocoagulation is an preferred technique for the treatment of ROP. Aim of this study to describe the result of laser indirect Ophthalmoscopy in Makassar, South Sulawesi, Indonesia. Methods : This is Observational retrospective study, from 1130 screening procedures during 2020 until 2022. This study found 41 ROP patients who had received therapy. Results : From 43 patients who received therapy, most were ROP stage 3 (80%), APROP (19%) and the rest were Stage IV A . 40 infants received lasers photocoagulation, and one infant received both laser photocoagulation and intravitreal anti-VEGF. Regression was found in all cases of stage 3 ROP. Patients with aggressive posterior ROP also were treated successfully, except one patient progressed to stage 4 ROP. Conclusion : with screening and prompt treatment, good outcomes have been obtained for infants with ROP